2017
DOI: 10.7748/ns.2017.e10939
|View full text |Cite
|
Sign up to set email alerts
|

Role of patient education in postoperative pain management

Abstract: Postoperative pain continues to be a significant issue in healthcare, with a considerable proportion of patients experiencing severe pain after surgery and finding pain management at home challenging. There are several barriers to effective pain management, involving both patients and healthcare professionals. Patient education may be a useful way to overcome many of these barriers. This article outlines the four stages of the education process, which can be used to provide patient education: assessing the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…It is disappointing to note that up to 6 months after surgery a quarter (25%) of patients still claimed that they would have liked more information about pain management, indicating that they may not have been sufficiently prepared for managing their pain at home. This lack of knowledge on pain management after discharge is in line with previous studies (Ingadóttir & Zoëga, 2017 ) and may suggest that even if nurses are aware of the importance of including pain management in their teaching, it does not result in an optimal self‐care outcome. To be effective, patient teaching about pain management requires thorough preparation and competence by nurses (Ingadóttir & Zoëga, 2017 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is disappointing to note that up to 6 months after surgery a quarter (25%) of patients still claimed that they would have liked more information about pain management, indicating that they may not have been sufficiently prepared for managing their pain at home. This lack of knowledge on pain management after discharge is in line with previous studies (Ingadóttir & Zoëga, 2017 ) and may suggest that even if nurses are aware of the importance of including pain management in their teaching, it does not result in an optimal self‐care outcome. To be effective, patient teaching about pain management requires thorough preparation and competence by nurses (Ingadóttir & Zoëga, 2017 ).…”
Section: Discussionsupporting
confidence: 86%
“…This lack of knowledge on pain management after discharge is in line with previous studies (Ingadóttir & Zoëga, 2017 ) and may suggest that even if nurses are aware of the importance of including pain management in their teaching, it does not result in an optimal self‐care outcome. To be effective, patient teaching about pain management requires thorough preparation and competence by nurses (Ingadóttir & Zoëga, 2017 ).…”
Section: Discussionsupporting
confidence: 86%
“…Effective communication between clinician and patient is thought to enhance compliance with treatment recommendations [50], satisfaction with care [51], overall treatment outcomes [52,53] and psychological well-being [51]. In addition, encouraging shared decisions may empower patients to become active participants in their own post-operative recovery and help to manage expectations of postoperative pain [54].…”
Section: Discussionmentioning
confidence: 99%
“…Parents may also benefit from other styles of novel intervention, such as YouTube videos, web pages, and smartphone applications. For example, studies have demonstrated the effectiveness of YouTube videos as a method of knowledge translation targeting parental pain management strategies, 35 explored the utility of web pages as a means of patient pain education, 36 and demonstrated the effectiveness of a smartphone application (Pain Squad+) in engaging adolescents in their own pain management processes. 37 There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 99%